Projeto e fabricação de uma bancada regulável para montagem de suspensão do tipo duplo “a” no chassi de um veículo tipo baja - Silva, Nilson Francisco da (Universidade Federal Rural do Semi-Árido, 2019)
In the field of mechanical engineering the design of a project is divided into several stages, where manufacturing is one of them, one of the tools most used in this stage are the templates, these have the function of ensuring the dimensions and parameters of the project during this process . The present work deals with the design and design of an adjustable bench (template) to assist the assembly and application of "A" double type suspension in BAJA type vehicles. This work presents in detail the bench applied in the prototype (SEVERO 19) of the Caraubaja SAE team. In addition, it shows in detail all steps to design this project, from preliminary studies, construction of the first components in CAD / CAE software (Autodesk Inventor) to fabrication, assembly, implementation (of the eyes and suspension) and tests in the prototype. The proposed project aims to be of easy manufacture, assembly and modulation. The project was validated comparing the virtual and real parameters of previous prototypes developed by the team, with the parameters of the new prototype which was used the bench in its design. At the end, it was verified the efficiency of the equipment, where it was obtained reductions considered in the relative error between the virtual and the real project, being that the caster that is a parameter associated to the angle of inclination of the amount, was the one that hears a greater reduction of variation.
Monografia
Keywords: Gabarito; Montante; Olhais; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA